Integrated Lean Management - Resilience Engineering Approach For Supply Chain Performance Improvement - Muhammad Wahyu Fauzi; Taufiq Immawan (Interdisciplinary Social Studies, 2025)
n the era of globalization and increasingly fierce competition, companies face complex challenges in managing supply chains that are both efficient and resilient to unexpected disruptions. Lean management approaches that focus on waste elimination can create vulnerabilities, while resilience engineering offers system robustness but potentially reduces efficiency. Purpose: This research aims to analyze the implementation of integrated lean management and resilience engineering approaches to improve supply chain performance holistically. Methods: The research employed a mixed methods approach with a before-after comparison study design conducted over 12 months in a manufacturing company. The research sample involved 16 respondents from various organizational hierarchy levels consisting of directors, managers, supervisors, and operational staff from five supply chain divisions (sales, procurement, production, warehouse, logistics). Results: The integrated implementation showed significant improvements across all divisions. The sales division experienced 39.7% sales growth, the production division achieved 117% productivity improvement with 54% lead time reduction, the warehouse division increased capacity by up to 1,400%, while the logistics division successfully minimized customer complaints and optimized operational costs. Overall, organizational performance improved from "Needs Improvement" category (195.12 points/39%) to "Adequate" category (343.56 points/69%). Conclusion: The integration of lean management and resilience engineering proved effective in improving supply chain performance through simultaneous optimization of operational efficiency and system resilience strengthening, creating a supply chain that is not only lean but also resilient.